(untitled) (Revista Brasileira Multidisciplinar, 2026)
The field of study "law and cinema" has grown significantly within the legal sphere. In this context, it is possible to observe its expansion in an interdisciplinary manner, especially in academic genres known as "law and literature." Given this, the present article explores the interconnections between these two fields to understand how cinematic narratives shape social and legal perceptions and provoke critical questions. The objective of this scientific paper is to analyze the mediation session procedure based on CNJ Resolution 125/2010, in dialogue with the film 7 Years, as well as its guiding principles. The methodology used is the analytical-interpretative approach proposed by Henriete Karam. The film explores methods of alternative dispute resolution, focusing on a conflict between the characters, where the mediator’s intervention is the only means to reach a solution. In this scenario, it is possible to identify the contribution of "law and cinema" as a representation of human experience and, in this particular case, reflect on the importance of mediation in social conflicts.